Ensiling for biogas production: Critical parameters. A review. (November 2016) - Teixeira Franco, Rúben; Buffière, Pierre; Bayard, Rémy
Abstract: In order to meet the legislative demands of new energy policy, investment in anaerobic digestion and biogas production has increased in recent years, making it a versatile and fully established technology. So as to remain competitive, anaerobic digestion should be optimized not only at the level of the process, but also down and upstream, in which biomass storage prior to digestion is included. Ensiling is a commonly used and promising techniques to store wet biomass before anaerobic digestion. This article reviews the crucial parameters for ensiling agricultural wastes and crops for biogas production, as source properties, storage management and duration, temperature or additives. According to the reported findings in the bibliography, feedstock and its biochemical characteristics will define the course of ensiling and the impact of other parameters during storage as well. Good silage preservation will occur for feedstocks with low moisture content, high accessible carbohydrates and low buffering capacity. High packing density and reduced particle size will contribute to minimize energy losses during ensiling. Additives are widely used but are not always an asset for methane potential conservation and their application should be more appropriate for poorly ensilable biomass. Finally, evidences suggest that under specific conditions, ensiling may increase methane potential despite non-negligible organic matter losses during storage. Exposing the answers given by the literature in terms of impact of different conditions in the course of ensiling and the questions still unresolved, this article highlights the good management practices of substrates for biogas production. Graphical abstract: Highlights: Biochemical properties of feedstock will define the course of ensiling. Good preservation requires low silage moisture, high water-soluble carbohydrates content and low buffering capacity. High packing density and reduced particle size minimize energy losses. Additives should be a potential asset for preservation of poorly ensilable biomass. Ensiling may be used as methane potential booster before anaerobic digestion.